Inward Looking Policies, Finite Change and Employment - The Capital Reallocation Effect - Sugata Marjit; Kausik Gupta (Center for Economic Studies and Ifo Institute (CESifo), 2020)
It is well recognized that there emerged a trend of inward looking trade policies even before COVID pandemic crippled the world. These were reflected in both BREXIT and US-China trade conflict. As countries become inward oriented, usually local prices start rising. With this backdrop this paper explores how rising local prices are likely to affect employment in the short and long run when we accommodate for finite change in a general equilibrium structure whereby sectors not only contract but might close down altogether due to capital reallocation effect following a price incentive. Mechanisms behind employment increase are very much different between the short and the long run. We discuss such mechanisms and results in a variety of structures essentially highlighting the significance of the extensive margin, targeted protection and non-traded good.
Keywords: F10; F11; F60; 330; price increase; finite change; employment; general equilibrium; product variety